A study of the Siege of Jerusalem in its physical, literary and historical contexts - Millar, Bonnie (2000)
The general perception of the Siege of Jerusalem is best summed up in Ralph Hanna's phrase that it is "the chocolate-covered tarantula of the alliterative movement". Only one critic has moved away from this consensus of opinion, Elisa Narin van Court, who argues "that in addition to the graphically violent anti-Judaism of the poem, there is a competing sympathetic narrative strand that complicates what has been considered a straightforward and brutal poetic." I follow Narin van Court in rejecting the standard opinion of the poem as a univocal narrative of unsavoury anti-Semitism and proceed to examine the poet's conception of his work, and how this poem differs from other accounts of the destruction of Jerusalem and the legend of Veronica. Pertinently, he uses different sources in an effort to bring out the contradictions latent in the story of the destruction of Jerusalem. He juxtaposes historical elements from the Polychronicon, such as the allusion to the tribute, with religious material in an attempt to query the necessity of war, even if the cause is ostensibly noble. Most notably, he raises the question of the motivation behind the campaign in Judaea. He avoids expressing value judgements, unlike texts such as the Vindicta Salvatoris and Titus and Vespasian which interpret the destruction of Jerusalem as the justifiable punishment of the Jews for the death of Christ. Not only is the poet's approach very different from that of literary and religious works, it also differs from that of historians. He is interested in people's motivation and how they react to the situations in which they find themselves. Hence he does not try to find overarching patterns in the siege of Jerusalem. The poem's literary context is of vital importance, for although the text bears certain similarities to works of crusading interest, such as the Charlemagne romances, it is nonetheless very different from them in terms of its attitude to non-Christians. The poet is anti-Judaic in that he believes that the Jewish religion is based on error and that the Jews were manifestly wrong in crucifying Christ, but he is still capable of making a distinction among them, seeing only their leaders as evil tyrants and expressing sympathy for the common citizens of Jerusalem. Thus he is not motivated by the anti-Semitism of the later Middle Ages, which led to accusations of host desecration, ritual murder and historiographic crucifixion being levelled against them. In this he differs from other redactions of the story of the destruction of Jerusalem, such as Titus and Vespasian and the accounts of medieval drama, which are virulently anti-Semitic as well as anti-Judaic in sentiment.